Internalisasi Nilai Kemuliaan Ilmu Dalam Pendidikan Islam: Perspektif Tarbawi Al-Qur’an Dan Hadis - Nazih, Nazih Sadatul Kahfi (Tarbawi, 2025)
The noble value of knowledge in Islam occupies a central position in the formation of civilisation and the character of a complete person. However, in contemporary educational practices, these noble values are often marginalised by pragmatic approaches that emphasise cognitive aspects alone. This article aims to examine in depth the internalisation of the noble value of knowledge in Islamic education based on the tarbawi perspective of the Qur'an and Hadith. This research uses a qualitative approach with a library research method, analysed through a thematic interpretation approach and a comparative study of classical and contemporary Islamic education literature. The results of the study show that knowledge in Islam is seen as a light (nūr) that guides humans towards spiritual and social perfection. Values such as sincerity, responsibility, and scientific integrity are key principles in the formation of civilised academics. This research contributes to the strengthening of a holistic Islamic education paradigm and provides a conceptual basis for value-based curriculum development. In conclusion, the internalisation of the noble value of knowledge should be the main orientation in the reform of Islamic education, with recommendations for further research that examines its empirical implementation in educational institutions.